1969
DOI: 10.1037/h0028296
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning and transfer of affective self-references in a role-played counseling interview.

Abstract: The differential effects of five forms of therapylike intervention (Um-Hmm, Echoic, Paraphrasic, combined Um-Hmm-Echoic, and combined Um-Hmm-Paraphrasic) in the conditioning and transfer of affective self-references (ASRs) were tested in a 40-minute role-played initial counseling interview. The 5s were 72 female student volunteers. Conditioning of ASRs and transfer to a TAT story telling task were found, although hypothesized relationships between discriminative cue potency of the interventions and performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
(11 reference statements)
1
8
0
Order By: Relevance
“…sponses (Crowley, 1970;Hackney, 1969;Hoffnung, 1969;Kennedy & Zimmer, 1968;Merbaum, 1963;Merbaum & Southwell, 1965;Pepyne, 1968; J. M. Rogers, 1960;Salzinger, 1960;Waskow, 1962). This research supports the training of counselors to produce verbal discriminative responses in systematic and contingent ways.…”
supporting
confidence: 51%
“…sponses (Crowley, 1970;Hackney, 1969;Hoffnung, 1969;Kennedy & Zimmer, 1968;Merbaum, 1963;Merbaum & Southwell, 1965;Pepyne, 1968; J. M. Rogers, 1960;Salzinger, 1960;Waskow, 1962). This research supports the training of counselors to produce verbal discriminative responses in systematic and contingent ways.…”
supporting
confidence: 51%
“…Several analogue studies have attempted to determine those counselor behaviors that produce greater discussion of feelings. Minimal verbal stimuli, such as "mm hmm," "go on," and "I see," when applied contingently immediately after the client's expression of feeling, have been found to be effective reinforcers of affect (Hoffnung, 1969;Kennedy & Zimnier, 1968;Rogers, 1960;Salzinger & Pizoni, 1960). Although these minimal verbal stimuli do occur during real counseling sessions, they are not representative of all the responses a counselor makes.…”
mentioning
confidence: 99%
“…Other studies have found conflicting results for the effects of more complex, noncontingent counselor statements, the most common of which are reflections, restatements, and probes. Some studies that measured reflection of feelings found increases in affect (Hoffnung, 1969;Merbaum, 1963;Merbaum & Southwell, 1965), whereas others found no increases (Barnabei, Cormier, & Nye, 1974;Waskow, 1962). Simi-This research was supported by a General Research Board grant from the University of Maryland.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In short, the counselor's use of reflection of feeling as a discriminative stimulus must result in certain predefined and desirable effects on client behavior. The likelihood that such responses emitted by the counselor do produce changes in client behavior within the interview has been demonstrated quite well in the verbal conditioning literature (Hoffnung, 1969;Kennedy & Zimmer, 1968). The question that remains unanswered is, What maintains the counselor's behavior?…”
Section: Discussionmentioning
confidence: 99%